A study of cardiovascular abnormalities among cirrhosis of liver cases - Raghavendra, .; Kotresh, N.; Naik, Shankar (International Journal of Advances in Medicine, 2016)
Background: The correlations between alcohol consumption and cirrhosis of liver have been dealt with great detail. As with the many studies that have looked upon the mortality of the patients with cirrhosis, the speed of progression of the disease and the various situations in which the condition of the patient deteriorates, many have been inconclusive about the reason for death in patients of cirrhosis of liver as the disease progresses. Methods: This study was conducted in the department of medicine, Vijayanagara Institute of Medical Sciences, a tertiary care hospital in Bellary, Karnataka Study subjects: were a group of 50 patients with alcoholic cirrhosis, a group of 50 patients with non-alcoholic cirrhosis and 50 normal subjects without cirrhosis. Results: The ECG findings among alcoholics, low voltage complex 10%, long QT3% LAE 8% LVH16%. ST T changes 10%. Among non-alcoholic patients low voltage complex 4% Long QT 2% LAE 7%, LVH 16% ST T changes 16%. Conclusions: The cardiovascular abnormalities did not show much difference between the alcoholic and non-alcoholic patients.